Scheme for generating a sequence of single photons of alternating polarization - Wilk, T; Specht, H; Webster, S; Rempe, G; Kuhn, A (2007)
Single-photons of well-defined polarization that are deterministically generated in a single spatio-temporal field mode are the key to the creation of multi-partite entangled states in photonic networks. Here, we present a novel scheme to produce such photons from a single atom in an optical cavity, by means of vacuum-stimulated Raman transitions between the Zeeman substates of a single hyperfine state. Upon each transition, a photon is emitted into the cavity, with a polarization that depends on the direction of the Raman process.